Representations of Power and Legacy: A Comparative Study of Ozymandias and Breaking Bad (2013) - Maulana Isyfa Raya; Sogimin Sogimin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the representation of power and legacy in Ozymandias and the Breaking Bad episode “Ozymandias,” aiming to identify their similarities and differences and to explore their intertextual relationship. Grounded in Michel Foucault’s concept of power and Julia Kristeva’s theory of intertextuality, this study employs a qualitative approach through comparative textual analysis of selected lines from the poem and dialogues from the series. The findings reveal that both texts construct power as dominant yet unstable and legacy as ultimately unsustainable. In the poem, power is symbolically expressed through “King of Kings” but undermined by “Nothing beside remains,” indicating its collapse over time. In contrast, the series represents power through Walter White’s verbal dominance, such as “I built this,” which is later challenged by other characters, leading to the breakdown of his control. In both texts, legacy fails to endure, as reflected in the ruined monument in the poem and the collapse of family and identity in the series. The study also shows that the relationship between the two works functions as a reinterpretation of classical themes within a contemporary context, demonstrating that power and legacy remain fragile despite differences in medium and representation.